Simply Constructing Li1.2Mn0.6Ni0.2O2/C Composites for Superior Electrochemical Performance and Thermal Stability in Li–Ion Battery. Issue 48 (21st December 2018) - Chen, Dandan; Xie, Dongjiu; Li, Guangshe; Zhang, Dan; Fan, Jianming; Li, Baoyun; Feng, Tao; Li, Liping
Abstract: A Co‐free Li‐rich cathode material Li1.2 Mn0.6 Ni0.2 O2 has been successfully modified by conductive acetylene black (CAB) using a simple physical grinding and post annealing process. X‐ray photoelectron spectroscopy (XPS), X‐ray absorption near‐edge structure (XANES) and Fourier transform infrared spectra (FTIR) characterizations show that annealing process leads to the formation of a strong chemical interaction between CAB and Li1.2 Mn0.6 Ni0.2 O2 . The modified sample with 5wt% CAB exhibits excellent cycle stability (83.9% capacity retention after 100 cycles at 1 C) and remarkable rate capacity (93.0 mAh g −1 at 10 C). At the same time, the thermal stability of pristine is obviously enhanced by modification with CAB. Such improvement is ascribed to the existence of the strong interaction between Li‐rich oxide and CAB. This work will offer hints for promoting the commercialization of Li‐rich cathodes. Abstract : CAB‐modified Li1.2 Mn0.6 Ni0.2 O2 was firstly obtained by a simple physical grinding and post annealing process. Carbon species around Li‐rich particles would bond with oxide and form a strong chemical interaction, which produces highly positive effect on electrochemical performance and thermal stabilty.